Archaeological and chemical investigation on the high imperial mosaic floor mortars of the domus integrated in the museum of archaeology D. Diogo de Sousa, Braga, Portugal - Fragata, Ana (2021)
This paper intends to characterize the floor mortar layers (nucleus, rudus and statumen) of the high imperial mosaics of the domus integrated in the Museum of Archeology D. Diogo de Sousa, the oldest roman housing testimonies known in Braga, Portugal. It offers an important archaeological and historical contextualization and first chemical characterization attempt on the mortars. The study of 13 mortar samples was carried out at a chemical level through X-ray fluorescence spectroscopy (XRF). All samples presented low lime content when compared to similar studies. A high chemical similarity between nucleus mortars (opus signinum) and chemical composition differences between rudus and statumen mortars was determined, confirmed by statistical analyses. Their composition was distinctly related to the stratigraphic position of each floor mortar layer, following Vitruvius’ model, and to the external conditions and treatments (e.g., capillary rise with soluble salts and application of chemical treatments), to which they were submitted.